Mathematical model for a new refrigeration compressor - Wibawa, Hutama Satria (2018)
The compressors have been widely used in refrigeration, heating and air compression industries. The development of compressors over the years has helped to improve quality of life. The demand for the compressor is expected to grow. As such, there is a demand to develop more efficient and cost-effective compressors. This project is a continuation of previous developments of the novel Coupled Vane Compressors. Firstly, a review of the existing compressors will be discussed and compared with the novel compressor. The detailed design, working principle and advantages of the Coupled Vane Compressor will be elaborated. The mathematical modelling of the coupled vane compressor will be formulated. The models consist of volume, thermodynamics, mass flow, flow area, geometric and dynamics model. The mathematical model will then be simulated using FORTRAN programming language. The simulation result will be presented and analyzed. The study will be focused on the vane design alternatives. A parametric study to find the optimum vane length will be discussed, and a comparative study between the vane designs will be conducted.